Lettere dalla Resistenza: un corpus inedito di scritture femminili e maschili - Veronica Bagaglini (MediAzioni)
The article analyzes the writings of female and male letters sent by partisans, mainly from Swiss internment camps between 1943 and 1944. The unpublished corpus is preserved at the Archivio Diaristico Nazionale of Pieve Santo Stefano (Arezzo). The analysis focuses on the contents and the linguistic varieties present in the collection. The letters are mostly addressed to a single partisan woman. They recount life in the camps, express concerns about the present and the future, ask news about the condition of friends, and convey the writers’ emotions, regardless of their gender. This is a correspondence between fellow fighters awaiting to return to the battlefield for their country’s liberation. From a linguistic perspective, deviations from the standard are not only determined by the writers’ socio-cultural background but also by the communicative situation in which the letters were written. The linguistic investigation aims to provide further testimony for the historical reconstruction of Italian popular writing and, in particular, partisan women’s writing.